Certification in endovascular hemostasis for trauma surgeons: Possible and practical?. Issue 5 (November 2021) - Herrold, Joseph Alden; Adnan, Sakib; Romagnoli, Anna; Madurska, Marta J.; Betzold, Richard; DuBose, Joseph; Scalea, Thomas; Morrison, Jonathan J.
Abstract : BACKGROUND: Endovascular hemostasis is commonplace with many practitioners providing services. Accruing sufficient experience during training could allow acute care surgeons (ACSs) to expand their practice. We quantified case load and training opportunities at our center, where dedicated dual-trained ACS/vascular surgery faculty perform these cases. Our aim was to assess whether ACS fellows could obtain sufficient experience in 6 months of their fellowship in order to certify in these techniques, per the requirements of other specialties. METHODS: We performed a retrospective case series where we reviewed 6 years (2013–2018) of endovascular activity at an academic, level I trauma center quantifying arterial access, angiography, embolization, stent and stent graft placement, and IVC filter procedures. This was compared with the certification requirements for interventional radiology, vascular surgery, cardiothoracic surgery, and interventional cardiology. RESULTS: Between 2013 and 2018, 1, 179 patients with a mean ± SD Injury Severity Score of 22.47 ± 13.24, underwent 4960 procedures. Annual rates per procedure, expressed as median (interquartile range), were arterial access 193.5 (181–195.5), diagnostic angiography 352 (321.5–364.5), embolization 90.5 (89.25–93.25), stent placement 24 (13.5–29.25), and IVC filter procedures 16.5 (10–23.75). Our 6-month case volume exceeded or was within 85% of the required number of cases for vascular surgery and interventional radiology training, with the exception of stent-graft deployment for both specialties, and therapeutic procedures for vascular surgery. CONCLUSION: The case volume at a large trauma center with a dedicated endovascular trauma service is sufficient to satisfy the case requirements for endovascular certification. Our trainees are already acquiring this experience informally. An endovascular trauma curriculum should now be developed to support certification within ACS fellowship training.